The educational perspective in community recreation/La perspectiva educativa en la recreación comunitaria - Rafael Fuentes Jordán; Alina Bestard Revilla (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The human being is a biopsychosocial and historical unit; as a social actor he is capable of reflecting and reproducing in his thinking and consciousness the surrounding reality of which he is a part, as well as exercising in it a transforming action called praxis. This is based as a problem on the lack of preparation of teachers in determining the contents of Physical recreation according to the real characteristics of the community context and to the objective and subjective historical conditions determined. The purpose of the article is to explain the link that education and its incidence have on the Physical recreation teacher, which has as a fundamental objective to solve the existing limitations in the program of the sport complex, from the content that is implemented, and to articulate the vertical and horizontal invariants, presented in the physical-recreational activities towards the community. The methodology consisted of an analysis of the teacher's way of acting in order to plan the activities in practice according to the integrating project of the combined sport complexes. The analysis showed insufficiencies in the selection of content as a dynamic tool within the community context to create a recreational and educational culture in free time. This had an impact on the improvement of the researched variable in 95% of the sample and was evaluated as very adequate. Based on this pre-experiment, it was concluded that the lack of preparation of the teacher affects the determination of the content of Physical recreation to generate alternatives in an educational way towards a correct constructive use of the community's free time.